Studi Penentuan Kalor Jenis Air dan Larutan Garam Menggunakan Mikrokontroler Arduino Uno - Valentinus Galih Vidia Putra; Andrian Wijayono; Endah Purnomosari; Ngadiono Ngadiono; Irwan Irwan (Program Studi Pendidikan Fisika STKIP Nurul Huda, 2019)
This research was conducted to determine specific heat of pure water and salt solution using the calorimeter measurement method based on the Arduino Uno microcontroller. The salt solution and pure water solution were heated by the heating wire with 2.4 A and 0.54 Ω. The temperature of the pure water and the salt solution was measured using the Arduino Uno microcontroller and DS18B20 temperature sensor. In this study, the Cv of pure water and salt solution has been found.